Genome-edited foods - Tuncel, A.; Pan, C.; Sprink, T.; Wilhelm, R.; Barrangou, R.; Li, L.; Shih, P. M.; Varshney, Rajeev K.; Tripathi, L.; Eck, J. van; Mandadi, K.; Qi, Y. (Springer, 2023)
Genome editing can transform agriculture and shape the future of food by improving crop yields and animal productivity, which in turn can help to achieve food security for the growing world population. CRISPR–Cas-based technologies are powerful gene editing tools that are applied to various food products. In this Review, we discuss the applications of CRISPR–Cas aimed at increasing the nutritional value of crops through macronutrient engineering and biofortification or the reduction of the amount of antinutrients. We examine the role of CRISPR–Cas in improving the flavour of crops and reducing post-harvest losses to increase consumer acceptance and decrease food waste. We also highlight the gene editing of animal food products and probiotics. We summarize the regulations for approval of gene-edited foods worldwide and the progressively evolving public view. Finally, we explore the strategies that can help to enhance the efficiency of genome editing techniques and the acceptance of genome-edited foods in the global market, and extend the technology to low-resource settings.